Contestation of Meanings in Procedural Democracy: Inter-Media Framing of President Prabowo’s Dialogue with Journalists - Joan Imanuel Edon; Ira Mirawati; Zidan Abdurrahman; Aditya Anggara R.B. (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study analyzes how Indonesian national media framed President Prabowo Subianto’s dialogue with seven senior journalists held in Hambalang on April 6, 2025, a moment positioned as a symbol of political openness during the early phase of his presidency. Employing a qualitative approach and Robert Entman’s framing analysis model, this research examines news coverage from six major media outlets — Kompas, Detik.com, IDN Times, Narasi, Liputan6, and TVOne — focusing on four framing dimensions: problem definition, causal diagnosis, moral evaluation, and treatment recommendation. The findings reveal a notable consensus across media in defining the core problem as a deficit in direct and transparent presidential communication on strategic national issues, with causes attributed to one-way and intermediary-based communication practices. However, variations emerge in moral judgments and proposed solutions, reflecting each outlet’s ideological orientation, editorial stance, and audience segmentation. While Kompas and Narasi adopt a more critical-constructive position emphasizing inclusivity and sustainability, IDN Times, Liputan6, and TVOne frame the dialogue more affirmatively as democratic progress, and Detik.com maintains a pragmatic and neutral tone. This study demonstrates that media framing of political dialogue is not neutral but constitutes a site of meaning contestation shaped by power relations. The findings contribute to political communication scholarship by highlighting how media simultaneously reproduce power narratives and perform a constrained watchdog role within Indonesia’s procedural democracy.